2023
DOI: 10.3390/biomedicines11030736
|View full text |Cite
|
Sign up to set email alerts
|

Lung microRNAs Expression in Lung Cancer and COPD: A Preliminary Study

Abstract: Non-small cell lung cancer (NSCLC) is one of the deadliest diseases worldwide and represents an impending burden on the healthcare system. Despite increasing attention, the mechanisms underlying tumorigenesis in cancer-related diseases such as COPD remain unclear, making novel biomarkers necessary to improve lung cancer early diagnosis. MicroRNAs (miRNAs) are short non-coding RNA that interfere with several pathways and can act as oncogenes or tumor suppressors. This study aimed to compare miRNA lung expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
0
6
0
1
Order By: Relevance
“…• miR 197-3p [111] • miR 199a-5p [111] • • miR 320a-3p [111] • • miR-34a-5p [111] • • miR 197-3p [111] • could significantly differentiate the immune cell proportions in the TME, including TILs [99], whereas the methylation of promoters CTLA4, LAG3, and PD-L1 was largely associated with longer survival and a longer duration of response when immunotherapy was used [100]. Some studies have shed light on the role of DNA methylation in COPD development and as a potential biomarker in patients with NSCLC and COPD [100][101][102], and the profiling of DNA methylation signatures in NSCLC and COPD patients revealed important differences between patients with or without COPD [101,102].…”
Section: Other Predictive Biomarkers Evaluated In Nsclc Patients With...mentioning
confidence: 99%
See 3 more Smart Citations
“…• miR 197-3p [111] • miR 199a-5p [111] • • miR 320a-3p [111] • • miR-34a-5p [111] • • miR 197-3p [111] • could significantly differentiate the immune cell proportions in the TME, including TILs [99], whereas the methylation of promoters CTLA4, LAG3, and PD-L1 was largely associated with longer survival and a longer duration of response when immunotherapy was used [100]. Some studies have shed light on the role of DNA methylation in COPD development and as a potential biomarker in patients with NSCLC and COPD [100][101][102], and the profiling of DNA methylation signatures in NSCLC and COPD patients revealed important differences between patients with or without COPD [101,102].…”
Section: Other Predictive Biomarkers Evaluated In Nsclc Patients With...mentioning
confidence: 99%
“…• miR 197-3p [111] • miR 199a-5p [111] • • miR 320a-3p [111] • • miR-34a-5p [111] • • miR 199a-5p [111] • •…”
Section: Other Predictive Biomarkers Evaluated In Nsclc Patients With...unclassified
See 2 more Smart Citations
“…It has been observed that high protein concentration in the everyday nutrition reduces COPD exacerbations 13 . Moreover; the nutritional status of lung cancer patients has been closely associated with treatment efficiency and survival 14 - 18 . In our current study we evaluated the chronic obstructive disease of the patients along with their cancer treatment and their nutritional status and metabolic rate, in an effort to identify how these three parameters interact.…”
Section: Introductionmentioning
confidence: 99%